External control during RWD/RWE research: a methodological approach - A. A. Zhuravkov; A. S. Kolbin (Качественная клиническая практика, 2022)
At the moment, randomized controlled trials (RCTs) are the gold standard for providing evidence of the effectiveness and safety of medicines. If it is impossible to randomize and create an internal control group, alternative methods of collecting evidence are used, for example, the use of so-called external control groups created, among other things, based on real world data (RWD). The increase in the number of studies using RWD and external control is clearly visible in oncology, where there are problems with randomization classically. Meanwhile, this trend is of concern and requires a better understanding of the acceptability of using external control groups and validation of RWD.